Detection of cardiac amyloidosis by PET/CT imaging using 124I-p5+14 peptide. (25th November 2020) - Wall, J; Martin, E.B; Stuckey, A; Richey, T; Williams, A.D; Whittle, B; Fu, Y; Powell, D; Heidel, R.E; Besozzi, M; Lands, R; Guthrie, S; et al.
Abstract: Introduction: Systemic amyloidosis is characterized by the deposition of protein fibrils in abdominothoracic organs, notably the heart, leading to organ dysfunction and significant morbidity. Patients who present with light chain (AL) amyloid-associated cardiomyopathy have a poor prognosis and median survival of only ∼ 9 mos. Cardiac amyloidosis is also present in many of the other forms of the disease and may be ever present in patients with transthyretin-associated amyloidosis (ATTR). Currently, no radiotracers are approved for the quantitative imaging of cardiac amyloid load. To address these needs, we have developed a synthetic amyloid-reactive peptide radiotracer, 124I-p5+14, suitable for PET/CT imaging. The peptide binds the three major forms of amyloid (AL, ATTR and ALECT2), as well as other, less common, types through multivalent electrostatic interactions with amyloid-associated glycosaminoglycans and fibrils. Herein we report safety, dosimetry, and efficacy data on the first 22 patients from the ongoing Phase 1, first-in-human trial of 124I-p5+14 in patients with systemic amyloidosis (NCT 03678259). Methods: Patients >18 years of age with a confirmed diagnosis of systemic amyloidosis and not requiring heparin therapy are eligible. Subjects received <2 mg of 124I-p5+14 (<2 mCi) administered as a single IV bolus. PET/CT images for the initial cohort (n=3) were acquired from 25 min to 48h post injection. The second cohort of patients were imaged at ∼5 h and 24 h post injection. Image data were acquired using a Biograph 16 PET/CT scanner with a low dose CT. Uptake of radiotracer in the left ventricular wall was performed by automated image segmentation and standard uptake value ratios (SUVR) were calculated using blood pool as the reference tissue. Results: To date, 22 patients (13 AL, 5 ATTR, and 4 other) patients have been evaluated. The gender-averaged mean whole body effective dose was 0.24 mSv/MBq. Cardiac uptake of the radiotracer was visually detected by a reader blinded to the patients' organ involvement in 85% and 100% of patients with AL and ATTR respectively, including patients with asymptomatic cardiac involvement - no cardiac symptoms or elevated cardiac biomarkers. The mean myocardium SUVR for visually positive AL and ATTR patients were 2.2±0.6 and 2.6±0.4. For visually negative AL patients the SUVRs were 1.0 and 0.9. In addition to cardiac amyloid, 124I-p5+14 uptake was observed in the nerves, ligaments, liver, spleen, adrenal glands, kidneys, pancreas, pituitary, and lung, with overall abdominothoracic organ-specific sensitivity of >90% based on clinical presentation. Sensitivity in the heart was 100%. Conclusions: PET/CT imaging of 124I-p5+14 provides excellent visualization of AL and ATTR cardiac amyloidosis which can be readily quantified as a means of monitoring response to therapy or disease progression. The 124I-p5+14 radiotracer was also capable of detecting amyloid in other abdominothoracic organs. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Heart Lung and Blood Institute, National Institutes of Health; ACTP Gift Fund at the UTGSM